Changes in the Level of Public Debt and Their Components in EU Countries for the Years 2000-2012 - Banaszewska , Monika (Studia Oeconomica Posnaniensia, 2014)
Due to the global financial and economic crisis the issue of public finance sustainability has gained special importance. One of the crucial components in the assessment of this stability is the ratio of public debt to GDP and its change over time. This article examines changes in the level of general government debt and their components in the European Union during the period 2000-2012. For this purpose, a statistical analysis of population structure and a one-dimensional analysis of variance were used.